Eficiência do coagulante orgânico extraído do engaço da uva no tratamento de efluente de vinícola e estabilização dos resíduos remanescentes da vinificação através de compostagem - Salton, Karine Zucco (2024)
Winemaking in Brazil is expanding, driven by the increase in grape growing areas and technological advances in wine production. However, waste resulting from winemaking, such as grape stalks, pomace, tree pruning and cafeteria represent an environmental and public health challenge if they are disposed of improperly. The objective of this research was to evaluate the effectiveness of an organic coagulant based on tannin extracted from grape stalks, comparing it with commercial tannin and aluminum sulfate in the treatment of effluents from a winery. Furthermore, the use of composting to treat winery`s waste was investigated, and a suitable composting yard was designed to process all waste generated by the company. The methodology used to extract the tannin coagulant included solid-liquid extraction with a hydroalcoholic solution as solvent, followed by filtration and concentration of the extract. For the tests, a pre-test was carried out using the Jar-test methodology, which simulates the coagulation, flocculation and sedimentation processes of a treatment plant to determine the ideal range of coagulant concentration and sedimentation time. With the concentration range and time identified, the Central Rotational Composite Design (RCD) was applied, where the concentrations to be tested and the times for analyzing the behavior of the treatments were defined. For composting, organic waste was sampled and analyzed both in the high and low seasons of the winery, thus making it possible to size the windrow, as well as the composting yard. The shape used by the windrow was triangular with 150 liters, where it remained under analysis and monitoring for 120 days. The results revealed an extract with a high concentration of condensed tannins, showing physicochemical properties suitable to be used as a coagulant in effluent treatment processes, as it demonstrated high efficiency in removing apparent color and turbidity, and showed promise in the parameters of chemical demand for oxygen and total phosphorus, as it presented a significant removal in some of the tests performed. The composting of winemaking residues was efficient, resulting in a compound with physical-chemical characteristics suitable for application to the soil. The design of the composting yard for the high and low seasons revealed that the investment required would be significantly high, due to the large amount of waste generated by the winery, however, the environmental and economic benefits that could be obtained with the commercialization of organic compounds, together with with the gains in terms of sustainability, would fully justify this investment. This study represents a significant contribution to the sustainable advancement of the wine industry by offering an alternative to value its waste and mitigate environmental impact.